Application of Compost and Dolomite Dosage on Chrysanthemum Plant Growth and Yield - Putu Gede Bayu Janardhana Dusak; Made Sri Yuliartini; I Gusti Made Arjana (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2025)
This study aims to determine the effect of applying compost and dolomite doses on the growth of chrysanthemum plants (Dendranthema grandiflora, Tzelev). This research was conducted in Pancasari Village, precisely in the Pudak Lestari Agro Ornamental Plant Farmers Group. This study employs a Group Randomized Design (GRC) consisting of two factors in a factorial arrangement. The first factor is compost (K), composed of 3 dosage levels, namely: K1= 2 tons ha-1, K2= 4 tons ha-1, K3= 6 tons ha-1, while the second factor is Dolomite (D), which consists of 3 dosage levels, namely: D1= 2 tons ha-1, D2= 4 tons ha-1, D3= 6 tons ha-1. The results showed that the interaction between compost and dolomite (KxD) had an intangible effect on all observed variables. The highest economic fresh weight of flowers was obtained in the treatment of compost fertilizer at a dose of 6 tons ha-1 (K3), which was 45.56 g, or an increase of 18.86% from the lowest economic fresh weight of flowers obtained at a dose of 2 tons ha-1 (K1), which was 38.33 g. Dolomite treatment provided the highest financial, fresh flower weight at a dose of 6 tons ha-1 (D3), which was 44.11 g, or an increase of 9.67% from the lowest economic, fresh weight obtained at a dose of 2 tons ha-1 (D1), which was 40.22 g.